Marketing Communication Strategy of Cihampelas Walk Bandung To Attract Visitors During the Covid-19 Pandemic Through the Bandung Plant Festival Event (Case Study at Cihampelas Walk Mall, Bandung) - Nursukma, Dianti Talitha (Budapest International Research and Critics University, 2022)
In general, this study aims to determine the form of planning, analyze the form of marketing communica-tion strategies and, examine the success of marketing communication strategies for the Bandung Plant Festival Event at Cihampelas Walk Bandung. This type of research is descriptive where this research has a main objective to describe the nature or temporary situation by walking at the time of the research be-ing conducted and examining the causes of a particular symptom. With this type of descriptive research, it will explain and describe the problems regarding how the marketing communication strategy of Cihampelas Walk Bandung in attracting visitors during the covid 19 pandemic. The data collection tech-niques used in this study were observation and interviews. Respondents in this study were one of the ten-ants at Cihampelas Walk, one of the sellers at the Bandung Plant Festival Event, and visitors to the Ban-dung Plant Festival. The results of this study are Ciwalk in attracting visitors during the Covid-19 pan-demic through the Bandung Plant Festival Event using planning by having a target audience, positioning and choosing an agency or work partner. The marketing communication strategy carried out by Ciwalk in attracting visitors during the Covid-19 pandemic through the Bandung Plant Festival Event by imple-menting market segmentation, event objectives, designing marketing communication messages, commu-nication channels, and marketing communication mix which contents such as event marketing, sales promotion, in-rect marketing, and digital marketing.